Kingdom of seashells: Explotation and culture of major commercial species - Nandini Padhi (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2021)
The beauty of hard outer protective layer of shells is admire by each and everyone. According to Hindu mythology some shells of Turbunaria sp.are believed to be the sacred reflection to the God Vishnu. From the ancient days the chank is considered as holy. Seashells are found in wide range of colors, sheds, tones and texture.